An International Comparison of Educational Systems: the Columbian, Iraqi and Kurdish cases - Mohammed, Peshawa Jalal; Casas, Jennyfer; Saleh, Sanaa Taler; Kovács, Karolina Eszter (Central European Journal of Educational Research, 2021)
As developing countries aim to improve their education to address the challenges of globalisation's economic and social demands, comparative education can provide references for reforms and changes. Through studying the educational systems of other countries, we can discover which reforms are possible and desirable. This article attempts to demonstrate some specific aspects of the educational systems of Columbia, Iraq and Iraqi Kurdistan and to compare them. It shows the decentralisation process and challenges of the systems. It also reveals the structure of education of the three systems and their differences related to duration and organisation of primary and secondary schools. Following that, the curriculum provision and their orientations are explained. Finally, the article also tries to find the differences in teacher training in terms of duration and training types, occurring before / during service. The obtained results show that the decentralisation process and its challenges are very similar in these educational systems while there are differences in the duration, structure, and curriculum subjects.